Al-Amr An-Nahy, Mujmal, dan Mubayyan - Zhafirah, Azka Ilma (IAINU Kebumen, 2024)
The science of Ushul Fiqh is a science that discusses the elaboration of rules in establishing Islamic sharia law which originates from the propositions of the Al-Qur'an. In the science of ushul fiqh there is a discussion of the istinbath method. Ushul fiqh experts have put the istinbath method into several categories, including Al-Amru Al-Nahyu and Mujmal Mubayyan. This research uses the Library Research or Literary Study method which is carried out by tracing sources related to Al-Amru Al-Nahyu and Mujmal Mubayyan. The results found are: Based on the research that has been carried out, it was found that what is meant by Al-Amru is the word command contained in the Al-Qur'an in conveying Islamic teachings which have been regulated by Allah and conveyed through the Al-Qur'an and Sunnah Prophet Muhammad SAW. while An-Nahy is the opposite of Al-Amru. namely prohibition. Prohibitions contained in the Koran for conveying Islamic teachings. and both have several types and rules that have been mentioned above. Meanwhile, mujmal and mubayyan are pronunciations that contain several conditions or laws contained in them, and it is not known what provisions have been agreed upon without further explanation (mubayyin).